THE MOST ANCIENT PLATYPERLIDAE (INSECTA, PERLIDA= PLECOPTERA) FROM EARLY LATE TRIASSIC DEPOSITS IN SOUTHERN SOUTH AMERICA (Ameghiniana, 2012)
The new insect species Platyperla marquati sp. nov. described herein is represented by a nymphal stage and belongs to the Order Perlida (= Plecoptera) Latreille (stoneflies). It comes from the uppermost section of the Potrerillos Formation, which crops out south of Cerro Cacheuta, at the southernmost end of the Precordillera (Mendoza Province, Argentina). The early Late Triassic Potrerillos/Cacheuta sedimentary succession in this area includes fluvial, deltaic and lacustrine facies that reflect deposition in the border of the Cacheuta depocenter of the Cuyo Basin. This is the second complete insect and the first autochthonous aquatic insect from Triassic beds in Argentina, and also the first record of the family Platyperlidae in Gondwana. This finding demonstrates the similarity of aquatic insect faunas in Mesozoic deposits all over the world, at least of the morpho-ecological types of the aquatic stages. The lacustrine insect fauna began evolving during the Triassic and became diverse during the Jurassic and Early Cretaceous. Detailed geological studies revealed that levels equivalent to the middle Triassic lower units of the Uspallata Group (Río Mendoza and Cerro de Las Cabras formations) lie exposed on the southeastern flank of Cerro Cacheuta. Therefore, a new geological map and interpretation for this area are also presented.Resumen. EL MÁS ANTIGUO PLATYPERLIDAE (INSECTA, PERLIDA= PLECOPTERA) EN DEPÓSITOS DEL TRIÁSICO SUPERIORTEMPRANO DEL SUR DE SUDAMÉRICA. El nuevo insecto aquí descripto, Platyperla marquati sp. nov., está representado por un estadio ninfal y pertenece al Orden Perlida (=Plecoptera) Latreille. Este ejemplar proviene de la sección superior de la Formación Potrerillos, que aflora en el sur del Cerro Cacheuta, en el extremo sur de la Precordillera (Provincia de Mendoza, Argentina). La secuencia sedimentaria Potrerillos/Cacheuta en esta área de edad Triásico Tardío temprano, comprende facies depositadas en ambientes fluvial, deltaico y lacustre en un borde del depocentro Cacheuta de la Cuenca Cuyana. Este es el segundo insecto completo y el primero típicamente acuático hallado en los niveles del Triásico de la Argentina y también el primer registro de la Familia Platyperlidae en Gondwana. El hallazgo demuestra las semejanzas de la fauna de insectos acuáticos durante el Mesozoico a nivel mundial, por lo menos con respecto a los tipos morfo-ecológicos de los sistemas acuáticos pasados. En el Triásico, la fauna de insectos lacustres comienza su evolución llegando a tener un mayor desarrollo durante el Jurásico y Cretácico Inferior. Estudios geológicos detallados han revelado que niveles equivalentes a las unidades inferiores del Grupo Uspallata (formaciones Río Mendoza y Cerro de Las Cabras) afloran en el flanco sureste del Cerro Cacheuta. Por lo tanto se presenta un nuevo mapa e interpretación geológica para esta área.